Handbook of Pharmaceutical Manufacturing Formulations. Volume Three, Liquid Products. - Niazi, Sarfaraz, 1949- (Milton : CRC Press LLC, 2019)
The Handbook of Pharmaceutical Manufacturing Formulations, Third Edition: Volume Three, Liquid Products is an authoritative and practical guide to the art and science of formulating drugs for commercial manufacturing. With thoroughly revised and expanded content, thisthirdvolume of a six-volume set, compiles data from FDA and EMA new drug applications, patents and patent applications, and other sources of generic and proprietary formulations including author's own experience, to cover the broad spectrum of cGMP formulations and issues in using these formulations in a commercial setting. A must-have collection for pharmaceutical manufacturers, educational institutions, and regulatory authorities, this is an excellent platform for drug companies to benchmark their products and for generic companies to formulate drugs coming off patent. Features: Largest source of authoritative and practical formulations, cGMP compliance guidance and self-audit suggestions Differs from other publications on formulation science in that it focuses on readily scalable commercial formulations that can be adopted for cGMP manufacturing Tackles common difficulties in formulating drugs and presents details on stability testing, bioequivalence testing, and full compliance with drug product safety elements Written by a well-recognized authority on drug and dosage form development including biological drugs and alternative medicines
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Pharmacology; Drugs -- Dosage forms